Quark-hadron mixed phases in protoneutron stars - Pagliara, Giuseppe; Hempel, Matthias; Schaffner-Bielich, Jürgen (Journal of physics. G, Nuclear and particle physics, 2010)
We consider the possible formation of the quark-hadron mixed phase in protoneutron stars. We discuss two cases. The first one, corresponding to a vanishingly small value of the surface tension of quark matter, is the well-known mixed phase in which the global electric charge neutrality condition is imposed. In turn, this produces a non-constant pressure mixed phase. In the second case, corresponding to very large values of the surface tension, the charge neutrality condition holds only locally. However, the existence in protoneutron star matter of an additional globally conserved charge, the lepton number, allows for a new type of non-constant pressure mixed phase. We discuss the properties of the new mixed phase and the possible effects of its formation during the evolution of protoneutron stars.
Gesehen am 23.06.2023